Discussions about reproductive and sexual health among young adult survivors of cancer. (21st February 2016) - Wang, Ying; Chen, Leo; Ruan, Jenny Y.; Cheung, Winson Y.
Abstract: Fertility preservation and sexual health are increasingly important as more young cancer patients survive their disease. Our aims were to describe the frequency with which reproductive and sexual health discussions occur, and to identify clinical factors associated with these discussions. Medical records of patients aged 20–39 diagnosed with solid tumors from 2008–2010 who survived ≥2 years were retrospectively reviewed. Multivariate logistic models were used to explore the relationship between clinical factors and occurrence of discussions. We analyzed 427 survivors: median age was 35 years, 29% were men, 88% had baseline [Eastern Cooperative Oncology Group (ECOG)] ECOG 0, and 79% were in a relationship. Only 58% and 7% of patients received discussions about reproductive and sexual health, respectively, at their initial oncology consultation, most of which were led by medical oncologists. There was a significant association between reproductive and sexual health conversations, in that those who engaged in dialog about one topic were more likely to participate in discussions about the other ( P = 0.01). Patients with gynecologic malignancies ( P < 0.0001) were more inclined to engage in sexual health discussions. Only a minority (19%) of patients took specific action toward fertility preservation, but the receipt of reproductive health discussions was a strong and independent driver for pursuing fertility preservation ( P < 0.0001). The impact of cancer and its treatment on fertility and sexual health was inadequately addressed at the time of diagnosis among young cancer survivors. This warrants specific attention since having reproductive health discussions was strongly predictive of patients pursuing fertility preservation strategies. Abstract : We reviewed medical records of young adult cancer survivors regarding reproductive and sexual health discussions with their physicians. Our study highlights that such conversations occur inadequately, even though this dialog is associated with a higher likelihood of fertility preservation strategies.